The Effect of Image Branding of Ambassadors for Reading Libraries on Visiting Interests of Users at University Library - Zafiratul Ashra; Purwaka Purwaka; Rahmat Alifin Valentino (Record and Library Journal, 2022)
Background of the study: The library reading ambassador is one form of promotion used by UPT. Bengkulu University Library to increase the interest of its users to visit. Reading ambassadors are required to have an image branding component in order to influence the interest of visiting users at UPT. Bengkulu University Library. This is the basis for researchers to measure how much the branding image of library reading ambassadors affects the interest of visiting users at UPT. Bengkulu University Library. Purpose: Measuring how much Image Branding of Duta Baca Library affects the interest of visiting users at UPT. Bengkulu University Library. Method: This study applies a quantitative method with a causal approach through multiple linear regression with the number of respondents being 100 UPT visitors. Bengkulu University Libraries were determined based on a stratified sample. Findings: The users feel that the branding image of the library reading ambassador is good enough so that it affects the interest of visiting users at UPT. Bengkulu University Library. This is sourced from the results of research conducted by the author based on the results of questionnaires from respondents. However, the results found show that the branding image of library reading ambassadors is not the main factor that influences the interest of users to visit. There are still other factors that influence the interest of users to visit UPT. Bengkulu University Library.  Conclusion: The results showed that the branding image of library reading ambassadors influenced the interest of visiting users at UPT. Bengkulu University Library with a strong level of interpretation with a coefficient of determination R square of 0.714